Reduction, fusion and raising in English and Spanish - Garrudo Carabias, Francisco (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 1991)
The reduction of clauses, together with the fusion of structures, is a source of syntactic problems especially isomorphism and structural ambiguity both in English and Spanish. Raising and Equi-NP Deletion are the processes responsible for them. Raising operates in English more often than in Spanish and under different conditions. The syntactic complication of these phenomena for a non-native speaker and the advantage of a possible reference to similar cases, although more restricted, in Spanish, makes a comparative study of these processes very useful. Ignoring the formal technicalities of Transformational Grammar, this paper analyses, compares and contrasts the conditions of operation of raising in English and Spanish.